2017
DOI: 10.1038/s41598-017-15079-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Parameters and Gut Microbiome Changes Before and After Surgery in Thoracic Aortic Dissection in Patients with Gastrointestinal Complications

Abstract: Thoracic aortic dissection (TAAD) is one of the most common types of aortic diseases. Although surgery remains the main method of treatment, the high rate of postoperative gastrointestinal complications significantly influences the effects of surgery and the recovery process. Moreover, the mechanisms underlying this disease remain unclear. To address these problems, we examined changes in the gut microbiota in 40 thoracic aortic dissection patients with abdominal complications after surgery. Levels of white bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Alistipes belongs to the Bacteroidetes and is often found in murine gastrointestinal tract microbiota samples (Lagkouvardos et al, 2016). Alistipes have recently been found to be increased in abundance in patients with gastrointestinal complications after thoracic aortic dissection surgery (Zheng et al, 2017), and are reported to be associated with human colorectal carcinoma (Shi et al, 2017). Alistipes have been shown to induce colitis and tumors in mice (Moschen et al, 2016) and were increased in mice exposed to ethanol (Peterson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Alistipes belongs to the Bacteroidetes and is often found in murine gastrointestinal tract microbiota samples (Lagkouvardos et al, 2016). Alistipes have recently been found to be increased in abundance in patients with gastrointestinal complications after thoracic aortic dissection surgery (Zheng et al, 2017), and are reported to be associated with human colorectal carcinoma (Shi et al, 2017). Alistipes have been shown to induce colitis and tumors in mice (Moschen et al, 2016) and were increased in mice exposed to ethanol (Peterson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of the statin group of drugs reduces IL-6 production but increases IL-10 and kynurenine (178). This expected opposite movement of IL-10 and IL-6 has been observed in IDO1-deficient DCs in which there is the anticipated loss of AHR activity and reduced levels of IL-10, but increased IL-6 and TNF-Ī± production (179); conversely both IL-6 and IL-10 were increased after surgery (180). Kynurenine itself suppresses IL-6 release but kynurenic acid has been reported to increase it.…”
Section: Malaria and Trypanosomiasismentioning
confidence: 97%
“…Fresh fecal samples (2 to 5 g) were immediately placed into a sterile sampling box, transferred by ice bath, and maintained at āˆ’80Ā°C until use, and the first fecal sample of each patient was collected before bowel preparation [ 11 ].…”
Section: Methodsmentioning
confidence: 99%